Pelatihan Optimalisasi Peran Bahasa dalam Penguatan Kesehatan Mental Pemuda Karang Taruna - Putriyanti, Lina; Fajriyah, Khusnul; Dhyah Yulianti, Padmi; Sari Setianingsih, Eka (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The training on optimizing the role of language in strengthening the mental health of youth in the Karang Taruna of Karanganyar Village was conducted to enhance participants’ awareness and ability to use language as a tool for emotional regulation, empathetic communication, and social support. This community service program involved 22 youths and was carried out through three stages: planning, implementation, and evaluation. The training employed interactive lectures, group discussions, simulations, and reflective activities, supported by pretest and posttest assessments. The pretest results showed an average score of 85.46, which increased to 94.71 in the posttest with a median score of 100, indicating a significant improvement in participants’ understanding. Demographic data revealed diverse age groups and professional backgrounds among participants, demonstrating the relevance of the program for a heterogeneous youth community. Beyond increasing knowledge, the training encouraged participants to apply positive and empathetic language in daily interactions and to recognize the importance of self-talk as part of mental well-being. These findings confirm that language-based literacy interventions are effective in strengthening youths’ psychological resilience and hold potential as a community empowerment model that can be replicated in other village settings.